2009
DOI: 10.2214/ajr.07.3502
|View full text |Cite
|
Sign up to set email alerts
|

CT Quantification of Emphysema in Young Subjects with No Recognizable Chest Disease

Abstract: Young healthy nonsmokers with no recognizable lung disease can also show a small proportion of emphysematous-like changes on CT densitovolumetry when a threshold of -950 HU is used. Reference values should be considered when applying the technique for early detection or grading of emphysema and when studying aging lungs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
49
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 39 publications
(51 citation statements)
references
References 38 publications
1
49
1
Order By: Relevance
“…(3,5) Interestingly, the age-related changes are remarkably homogeneous, as opposed to the irregular distribution of airspace enlargement in emphysema. (5) The EI values observed in our cohort of patients were higher than were those reported in a study involving single-slice CT (22) and lower than were those reported in a study involving HRCT. (24) Factors that might have influenced the results include the reconstruction algorithm, radiation dose, collimation, CT scan manufacturer, and HU range selected for lung segmentation.…”
Section: Resultscontrasting
confidence: 61%
See 4 more Smart Citations
“…(3,5) Interestingly, the age-related changes are remarkably homogeneous, as opposed to the irregular distribution of airspace enlargement in emphysema. (5) The EI values observed in our cohort of patients were higher than were those reported in a study involving single-slice CT (22) and lower than were those reported in a study involving HRCT. (24) Factors that might have influenced the results include the reconstruction algorithm, radiation dose, collimation, CT scan manufacturer, and HU range selected for lung segmentation.…”
Section: Resultscontrasting
confidence: 61%
“…(18,20,21,27,28) The software used in the present study segments the lungs within a range of −1,024 HU to −400 HU, which results in a TLV that is lower than is that obtained with lung segmentation within a range of −1,024 HU to −250 HU. (22) Therefore, although lung volumes can be similar at densities below −950 HU, proportional differences among TLV values can be observed at higher densities.…”
Section: Resultsmentioning
confidence: 97%
See 3 more Smart Citations